Local government and national parks – how to break the deadlock in cooperation? - Kachniarz, Marian (Samorząd terytorialny a parki narodowe – jak przełamać impas we współpracy?, 2025)
Aim: The article analyses the stunted development of Poland's network of national parks, identifying key barriers to their expansion and proposing specific directions for corrective action, and highlights the unique role of national parks in environmental protection while pointing out that in Poland their share of the area is only 1.05%, which is significantly below the European Union average. Methodology: The research included an analysis of the legal and economic aspects and a literature review, to identify the main problems limiting the development of national parks. Particular attention was paid to barriers stemming from resistance by local governments, the loss of forest tax revenues, and discrepancies in salaries between employees of national parks and State Forests. Results: It was found that effective ways to overcome these challenges comprise introducing financial support mechanisms for local communities and fostering partnerships between the national parks and local governments. The findings suggest that changing the approach of the central administration and implementing a management model based on cooperation and dialogue could effectively revitalise the development process of national parks. Implications and recommendations: The proposed solutions can be applied not only in Poland but also in other countries facing similar challenges. Implementing financial support mechanisms and a partnership-based model could enhance environmental protection and foster harmonious collaboration between national parks and local communities. Originality/value: The strengths of this paper stems from its comprehensive, integrated analysis of the stagnation of national park development in Poland, which uniquely takes into account legal, economic, and socio-political factors. By reframing the creation of national parks as a process based on cooperation rather than antagonism, the article presents innovative theoretical and practical strategies that can be applied in Poland and countries facing similar challenges, balancing ecological goals with socio-economic realities.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 86-96
Keywords: national park; local government; governance; eco-compensation; park narodowy; samorząd lokalny; współzarządzanie; eko-kompensacja